Pre-synaptic GABAA in NaV1.8+ primary afferents is required for the development of punctate but not dynamic mechanical allodynia following CFA inflammation - Liu, Sheng; Bonalume, Veronica; Gao, Qi; Chen, Jeremy Tsung-Chieh; Rohr, Karl; Hu, Jing; Carr, Richard (Cells, 2022)
Hypersensitivity to mechanical stimuli is a cardinal symptom of neuropathic and inflammatory pain. A reduction in spinal inhibition is generally considered a causal factor in the development of mechanical hypersensitivity after injury. However, the extent to which presynaptic inhibition contributes to altered spinal inhibition is less well established. Here, we used conditional deletion of GABAA in NaV1.8-positive sensory neurons (Scn10aCre;Gabrb3fl/fl) to manipulate selectively presynaptic GABAergic inhibition. Behavioral testing showed that the development of inflammatory punctate allodynia was mitigated in mice lacking pre-synaptic GABAA. Dorsal horn cellular circuits were visualized in single slices using stimulus-tractable dual-labelling of c-fos mRNA for punctate and the cognate c-Fos protein for dynamic mechanical stimulation. This revealed a substantial reduction in the number of cells activated by punctate stimulation in mice lacking presynaptic GABAA and an approximate 50% overlap of the punctate with the dynamic circuit, the relative percentage of which did not change following inflammation. The reduction in dorsal horn cells activated by punctate stimuli was equally prevalent in parvalbumin- and calretinin-positive cells and across all laminae I-V, indicating a generalized reduction in spinal input. In peripheral DRG neurons, inflammation following complete Freund’s adjuvant (CFA) led to an increase in axonal excitability responses to GABA, suggesting that presynaptic GABA effects in NaV1.8+ afferents switch from inhibition to excitation after CFA. In the days after inflammation, presynaptic GABAA in NaV1.8+ nociceptors constitutes an “open gate” pathway allowing mechanoreceptors responding to punctate mechanical stimulation access to nociceptive dorsal horn circuits.